THE EFFECT OF RETURN ON ASSEST (ROA) AND RETURN ON EQUITY (ROE) ON COMPANY VALUE - Mardhati Fatila; Syahril (SEAN Institute, 2022)
The success of financial management in managing financial performance affects the value of the company. The higher the value of the company, the higher the company's interest by investors so that the share price rises and the prosperity of shareholders is higher. In this study, the ROA and ROE ratios are used as part of financial performance to determine their effect on firm value in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The hypothesis testing of this study uses the t-test and f-test, with the IBM SPSS Statistics 20 application tool. This study uses a quantitative method with a sample of 10 companies that have the largest profits for the 2019-2021 period. This study uses hypothesis testing H0 and H1, with a significance value of 5%. The results of the tests that the authors did regarding the effect of ROA and ROE on firm value can be concluded that ROA has a positive and significant effect on firm value with a significance of 0.00 (less than 0.05) and ROE has a negative and significant effect on firm value with a significance of 0.00 (less than 0.05). So it can be concluded that based on the value of ROA, financial management succeeded in maximizing the value of the company while based on the value of ROE, the management of the company has not succeeded in maximizing the value of the company. 05) and ROE have a negative and significant effect on firm value with a significance of 0.00 (smaller than 0.05). So it can be concluded that based on the value of ROA, financial management succeeded in maximizing the value of the company while based on the value of ROE, the management of the company has not succeeded in maximizing the value of the company. 05) and ROE have a negative and significant effect on firm value with a significance of 0.00 (smaller than 0.05). So it can be concluded that based on the value of ROA, financial management succeeded in maximizing the value of the company while based on the value of ROE, the management of the company has not succeeded in maximizing the value of the company.